Atmospheric Non‐Equilibrium Plasma Promotes Cell Death and Cell‐Cycle Arrest in a Lymphoma Cell Line. Issue 12 (15th June 2015) - Gherardi, Matteo; Turrini, Eleonora; Laurita, Romolo; De Gianni, Elena; Ferruzzi, Lorenzo; Liguori, Anna; Stancampiano, Augusto; Colombo, Vittorio; Fimognari, Carmela
Abstract : Atmospheric non‐equilibrium plasma is drawing interest as a promising tool for cancer treatment due to its blend of physical and chemical components that can exert anti‐tumor effects. In this work, we investigate the effects of plasma treatment, performed by means of a wand electrode DBD driven by nanosecond high voltage pulses, on the viability, proliferation, and cell‐cycle distribution of cells of mouse lymphoma. Results for direct treatment, with cell exposed to plasma while suspended in culture medium, and indirect treatment, where cells were added to culture medium previously activated by plasma treatment, are compared. A qualitative characterization by means of high‐speed and iCCD imaging of the plasma discharges produced for the different operating conditions adopted in biological experiments, as well as a semi‐quantitative study of the reactive species produced by plasma treatment in the culture medium, are also presented. Abstract : Fundamental aspects of plasma interaction with cancer cells are investigated using a wand electrode DBD driven by nanosecond HV pulses . Viability, proliferation, and cell‐cycle distribution of mouse lymphoma cells are measured after plasma treatment. Results of cell viability for direct and indirect plasma treatments are compared. HS and iCCD images of plasma discharges generated under the operating conditions adopted in biological experiments are presented.